Confissão mal disfarçada? A autorrepresentação e a busca de identidade nos romances Recordações do Escrivão Isaías Caminha e Clara dos Anjos, de Lima Barreto - Silva, Kessya Steicy Batista (2023)
Lima Barreto was a writer who allowed himself to go beyond literary work and made his literature an instrument of militancy in the face of various problems in society, such as racism. As a result, his literature remained forgotten for years due to the silencing of literary critics at the time. From his biographer, Francisco de Assis Barbosa, and from social movements that had repercussions in Brazil, his literature was rescued, and along with it black-Brazilian literature gained strength in the country. Increasingly, this literature has gained space not only in popular taste, but also in the academic environment; therefore, important elements that are part of it have been discussed. In this context, black writers, such as Lima Barreto, still find resistance not only in the nomenclature “Black-Brazilian Literature”, but also in the literary work of the black author. Based on this issue, the present work seeks to analyze self-representation and racial identity of characters in the novels Recordações do Escrivão Isaías Caminha and Clara dos Anjos, by Lima Barreto. For this, a vast theoretical foundation on black-Brazilian literature was used to subsidize such elements, which are not only present in Lima Barreto’s literary project, but in black-Brazilian literature itself. For this purpose, theorists such as Cuti (2010), Duarte (2011), Ianni (1988) are present, among other authors. In addition, this research also focuses studies on the novel elements: narrator, character and space within the works chosen here, with the intention of comparing how these two novels are similar and different. Since the two novels have a common objective when it comes to the characters and Lima Barreto's literary project. For that, Candido (2014), Lins (1976), Reuter (1995, 2002) and others were used as a theoretical foundation. Furthermore, the research addresses the study of symbols, which plays an important role in understanding the symbolism behind the novelistic works worked here and understanding how such elements are fundamental to understanding the protagonists' search for identity. For this, studies by Mandarino and Gomberg (2009) were used. Besides, the present work discusses the racial identity of the protagonists who, initially, in the novels are revealed, but when they come into contact with elements of the narrative they become aware of their identity. For this, authors such as Bauman (2021), Fanon (2020), Munanga (2020) were used, among other authors. It was concluded that Recordações do Escrivão Isaías Caminha and Clara dos Anjos are similar works not only in the narrative trajectory, but in the role they play for the reader, in making them aware of their identity in society. Thus, it can be said that Lima Barreto formulated, through self-representation, a discussion about the social and racial problems of his time. Furthermore, the author seeks in these two novels to give a destiny not only to the characters, but to the black people.